Facial masks in children: the position statement of the Italian pediatric society - Alberto Villani; Elena Bozzola; Annamaria Staiano; Rino Agostiniani; Antonio Del Vecchio; Nicola Zamperini; Francesco Marino; Davide Vecchio; Giovanni Corsello (BMC, 2020)
Abstract Facial masks may be one of the most cost-effective strategies to prevent the diffusion of COVID 19 infection. Nevertheless, fake news are spreading, alerting parents on dangerous side effects in children, such as hypercapnia, hypoxia, gut dysbiosis and immune system weakness. Aim of the Italian Pediatric Society statement is to face misconception towards the use of face masks and to spread scientific trustable information.